2019
DOI: 10.1109/access.2019.2950371
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Automatic Outlining Agricultural Parcels: Exploiting the Land Parcel Identification System

Abstract: Accurate and up-to-date information on the spatial and geographical characteristics of agricultural areas is an indispensable value for the various activities related to agriculture and research. Most agricultural studies and policies are carried out at the field level, for which precise boundaries are required. Today, high-resolution remote sensing images provide useful spatial information for plot delineation; however, manual processing is time-consuming and prone to human error. The objective of this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 46 publications
0
25
0
10
Order By: Relevance
“…The filter weight and length have to be smaller than those of the input sub-images. [47]. Each input layer is normalized by using the mean ( ) and standard deviation (or variance -) parameter of the values in the current batch based on the following formula: whereas the and are trainable parameters, ̂ can be calculated by using mean ( ) and variance ( 2 ) of mini-batch B = {x1…m} as following formula:…”
Section: E U-net Architecture For Land-cover Detectionmentioning
confidence: 99%
“…The filter weight and length have to be smaller than those of the input sub-images. [47]. Each input layer is normalized by using the mean ( ) and standard deviation (or variance -) parameter of the values in the current batch based on the following formula: whereas the and are trainable parameters, ̂ can be calculated by using mean ( ) and variance ( 2 ) of mini-batch B = {x1…m} as following formula:…”
Section: E U-net Architecture For Land-cover Detectionmentioning
confidence: 99%
“…Gracia-Pedrero et al employ a U-Net architecture to segment images into three classes: field, buffered boundary, and background. The boundaries are then computed from the contour of the first class (García-Pedrero et al, 2019). Likewise, in (Waldner, Diakogiannis, 2019), Waldner and Diakogiannis adapt a U-Net model to generate not only segmented images, but also predict distances to the field boundaries.…”
Section: Related Workmentioning
confidence: 99%
“…Within the LPIS framework, most member states of the European Union makes publicly available datasets of agricultural parcels, which inform on their crop types and geometries. This dataset has been used before in the relevant literature (García-Pedrero et al, 2019). This work also used this source, more specifically, the French and Danish datasets for the year 2018 2 and 2019 3 respectively.…”
Section: Study Area and Materialsmentioning
confidence: 99%
“…Deep learning can reduce the manual manipulation of data as, in this method, the importance of each dataset is automatically managed by neural networks. Several studies have shown that deep learning can solve previously challenging issues in the fields of engineering [17] , manufacturing [18] , [19] , [20] , transportation [21] , [22] , [23] , agriculture [24] , [25] , [26] , and medicine [27] , [28] , [29] , [30] .…”
Section: Introductionmentioning
confidence: 99%